2008
DOI: 10.1074/jbc.m801240200
|View full text |Cite
|
Sign up to set email alerts
|

Structure- and Substrate-based Inhibitor Design for Clostridium botulinum Neurotoxin Serotype A

Abstract: The seven antigenically distinct serotypes of Clostridium botulinum neurotoxins cleave specific soluble N-ethylmaleimidesensitive factor attachment protein receptor complex proteins and block the release of neurotransmitters that cause flaccid paralysis and are considered potential bioweapons. Botulinum neurotoxin type A is the most potent among the clostridial neurotoxins, and to date there is no post-exposure therapeutic intervention available. To develop inhibitors leading to drug design, it is imperative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
97
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(107 citation statements)
references
References 48 publications
10
97
0
Order By: Relevance
“…A quick look at the sequences of the products suggested that acetyl-SNKTRIDEANQ with two acidic residues and two acid amides might have a preferential interaction with the highly positively charged LcA C terminus (KNFTGLFEFYKLLCVR-GIITSKTKSLDKGYNK). Lack of electron density of LcA residues 420 -448 in the crystal structure of BoNT/A (9) and failure of full-length LcA to form crystals (12,13,33) suggest that the LcA C terminus is highly mobile. Our results of the thermal denaturation experiment described in Fig.…”
Section: Isothermal Titration Calorimetry For the Binding Of Lca Ctermentioning
confidence: 99%
See 3 more Smart Citations
“…A quick look at the sequences of the products suggested that acetyl-SNKTRIDEANQ with two acidic residues and two acid amides might have a preferential interaction with the highly positively charged LcA C terminus (KNFTGLFEFYKLLCVR-GIITSKTKSLDKGYNK). Lack of electron density of LcA residues 420 -448 in the crystal structure of BoNT/A (9) and failure of full-length LcA to form crystals (12,13,33) suggest that the LcA C terminus is highly mobile. Our results of the thermal denaturation experiment described in Fig.…”
Section: Isothermal Titration Calorimetry For the Binding Of Lca Ctermentioning
confidence: 99%
“…However, when the catalytic activity was measured on an intermediate-sized peptide substrate, a 1-425-residue LcA displayed only 25% of the activity, 4 and a 1-424-residue construct displayed 25% of the fulllength LcA activity as well (12). Thus, it is important that this anomaly is more thoroughly investigated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5 DOVIS was used to systematically dock the MLSMR compounds to the catalytic binding site of the BoNTA protein target (PDB code 3C8A). 6 The compounds were sorted by AutoDock 4.0 score, 7 and the top 20000 compounds were chosen and minimized within a fixed BoNT/A catalytic site. After minimization, the compounds were rescored with three different scoring functions, AutoDock 4, 7 LigScore 2, 8 and X-Score.…”
mentioning
confidence: 99%